Di-George syndrome presenting with hypocalcaemia in adulthood: two case reports and a review. Issue 6 (25th May 2005) - Kar, P S; Ogoe, B; Poole, R; Meeking, D
Abstract : This report describes two cases of Di-George syndrome presenting with hypoparathyroidism in adulthood. The first patient presented with profound hypocalcaemia that resulted in a generalised seizure. Routine investigations revealed hypoparathyroidism. The clue to her underlying condition was the postnatal death of her young child. This case shows that Di-George syndrome can present in adulthood with hypocalcaemia in the absence of other classic features of this condition. This has enormous implications for future family planning and may also have important health implications. The second patient, diagnosed on routine blood testing, had previously suffered with a congenital heart condition, but the syndrome was not revealed until she was of postmenopausal age. These two patients show that Di-George syndrome can present in adulthood with hypocalcaemia. This is an important observation because the condition has profound implications for health and family planning.